Understanding the chemistry & pharmacology of antibody–drug conjugates in triple-negative breast cancer with special reference to exatecan derivatives - Sawant S.; Naik G.G.; Sahu A.N.; Jagtap V.A. (My University, 2025)
In the spectrum of breast malignancies, triple-negative breast cancer is the most widely spreading subtype of breast cancer due to a low availability of therapeutic remedies. Recently, antibody–drug conjugates dramatically resolved the landscape for the treatment of triple-negative breast cancer. This review mainly focuses on the chemistry, structure, mechanism of action, and role of antibody–drug conjugates in triple-negative breast cancer. Datopotecan Deruxtecan (Dato-DXd) is a new-generation ADC showing encouraging results for TNBC. In this review, we have also emphasized TROP-2-directed Datopotamab deruxtecan ADCs to treat triple-negative breast cancer, its synthesis, mechanism of action, pharmacokinetics, pharmacodynamics, adverse events, and their ongoing clinical trials. Graphical abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.